Pemberdayaan Organisasi PKK dan UMKM Milik Bu Sri; Upaya Perbaikan Keterlibatan Wanita di Desa Setren - Shafira Rahmawati; Moy Yustiwa; Nadya Putri; Fairuz Sany; Nidya Arum; Hendra Maulana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Women's empowerment is a modern concept that marks progressive changes in efforts to liberate from patriarchal culture, where women's involvement in society was previously very minimal. Efforts to align the portion of involvement of all genders are often referred to as the equal rights movement or women's liberation movement. In Setren Village, women's involvement is still low, with the achievement of SDG 5 point